The relationship between sexual function and sexual dysfunction beliefs after postpartum in primiparous women - Elahe Amirkhalili; Mansoureh jamshidimanesh (مراقبت پرستاری و مامایی ابن سینا)
Background and Objective: Women's sexual functioning changes after childbirth, and various factors play a role in it. The aim of this study was to determine the relationship between sexual functioning and dysfunctional sexual beliefs after childbirth. Materials and Methods: This cross-sectional study was conducted on 352 primiparous women after childbirth in 14 selected healthcare centers affiliated with the Iran University of Medical Sciences using a multi-stage sampling method. The data collection tools included a demographic questionnaire, pregnancy history, dysfunctional sexual beliefs, and a sexual functioning index. Data analysis was performed using SPSS 24 software, and the data were described using means, standard deviations, frequencies, and percentages. A stepwise multiple linear regression model was used to assess the relationship between sexual functioning variables and dysfunctional sexual beliefs. A significance level of less than 0.05 was considered. Results: In this study, 19 percent of women had dysfunctional sexual beliefs, and 73 percent had undesirable sexual functioning. There was a significant correlation between dysfunctional beliefs and sexual functioning in primiparous women after childbirth (p = 0.001, β = -0.237), predicting a 10 percent variance in sexual functioning. Conclusion: In this study, dysfunctional sexual beliefs were relatively high among primiparous women within 2 to 12 months after childbirth. Due to its association with sexual dysfunction, it seems that sexual beliefs should be addressed in marital counseling and throughout pregnancy.